Indonesian Model of Foreign Direct Inverstment (Omnibus Law): Learning From Singapore - Diana Setiawati; Hary Abdul Hakim (Universitas Muhammadiyah Bima, 2023)
Foreign direct investment (“FDI”) has become a hot topic in board meetings all over the world as modern businesses are seizing new opportunities within theglobalized economy. The modern economy functions ona larger scale than ever before, and companies are beginning to realize that failing to partake in foreigndirect investment could lead to their demise. FDI has been a key factor driving export-led growth in Southeast Asia. This research offers a comparative legal and critical analysis of the Foreign Direct Investment Regulation (FDI) and strategies of attracting FDI in Indonesia by learning from Singapore. Indonesia has been striving to attract FDI, and therefore on October2020 Indonesia ratified the Omnibus Law on JobCreation replacing 79 acts regarding investment. Nevertheless, this law has raised legal controversies andpublic protests. This research focuses finding a model ofFDI attraction for Indonesia through lessons learnedfrom Singapore in terms of how to attract FDI. Singapore have made remarkable FDI accomplishmentthrough their own ways. The result of this research isaims to deplore the reasons for the accomplishment, intending to find a better model for Indonesia than theOmnibus Law currently adopted. This research arguesthat Indonesia should reconsider the Omnibus Law approach by referring to the lessons learned from theexperience of Singapore’s success in attracting FDI.